Opera Production in Ireland: No Place for Politics? (Journal of the Society for Musicology in Ireland, 2010)
Opera has a history of just over four hundred years and a markedly finite canon in comparison with spoken theatre. The repertory has expanded very little in the past half-century, and this means that renewal is largely achieved through direction and design. In continental European theatres, and in Germany in particular, operas constantly acquire new layers of meaning in production, and are often staged as political statements. In Ireland, this type of ‘director’s theatre’ is rare. Irish companies seldom see opera as a vehicle for clear ideological statements, and productions often shy away from the political potential of opera texts. Drawing on theatre, opera and performance theory by Keir Elam, David J. Levin and Jon McKenzie among others, this article takes four recent Irish opera productions as case studies and argues that even apparently apolitical opera is inevitably shaped by politics.